2019
DOI: 10.1186/s12866-019-1632-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics resistance and toxin profiles of Bacillus cereus-group isolates from fresh vegetables from German retail markets

Abstract: BackgroundThis study aimed to evaluate the safety of raw vegetable products present on the German market regarding toxin-producing Bacillus cereus sensu lato (s.l.) group bacteria.ResultsA total of 147 B. cereus s.l. group strains isolated from cucumbers, carrots, herbs, salad leaves and ready-to-eat mixed salad leaves were analyzed. Their toxinogenic potential was assessed by multiplex PCR targeting the hemolysin BL (hbl) component D (hblD), non-hemolytic enterotoxin (nhe) component A (nheA), cytotoxin K-2 (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
82
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 40 publications
25
82
8
2
Order By: Relevance
“…Moreover, the prevalence of the nheABC cluster in our isolates is higher than that in food products of Poland (78.6% for nheABC ; Berthold-Pluta et al, 2019 ). cytK - 2 was detected in 93.1% of the isolates (256/275), which is much higher than the rate of previous reports (37.4–73%; Gao et al, 2018 ; Fiedler et al, 2019 ; Yu et al, 2019 ). Moreover, the proportion (>5%; 14/275) of the emetic strain is higher than the general level around the world ( Chaabouni et al, 2015 ; Fiedler et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Moreover, the prevalence of the nheABC cluster in our isolates is higher than that in food products of Poland (78.6% for nheABC ; Berthold-Pluta et al, 2019 ). cytK - 2 was detected in 93.1% of the isolates (256/275), which is much higher than the rate of previous reports (37.4–73%; Gao et al, 2018 ; Fiedler et al, 2019 ; Yu et al, 2019 ). Moreover, the proportion (>5%; 14/275) of the emetic strain is higher than the general level around the world ( Chaabouni et al, 2015 ; Fiedler et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 62%
“…cytK - 2 was detected in 93.1% of the isolates (256/275), which is much higher than the rate of previous reports (37.4–73%; Gao et al, 2018 ; Fiedler et al, 2019 ; Yu et al, 2019 ). Moreover, the proportion (>5%; 14/275) of the emetic strain is higher than the general level around the world ( Chaabouni et al, 2015 ; Fiedler et al, 2019 ). The cesB -positive strains we isolated had both psychrotrophic and mesophilic signatures ( Table 2 and Supplementary Figure S4 ), corresponding to an intermediate genotype according to von Stetten et al, 1998 .…”
Section: Discussioncontrasting
confidence: 62%
“…The growing antimicrobial resistances in modern clinical pathology and medicine interest and focus on bioactive compounds from natural products in order to generate new and novel antimicrobials in general and particular antibiotics (Fiedler et al 2019). Bacilli have capability able to synthesis more than two dozen of antibiotics with variety in function and structures as they well known for the production of a vast array of structurally unrelated antimicrobial compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The MIC test was susceptible to tetracycline (8.0 mg / litre), vancomycin (4.0 mg / litre), and gentamicin (4.0 mg / litre), but was streptomycin resistant (Adimpong et al, 2012). Moreover, disc diffusion assay was reported for antibiotic resistance profiles in the genus of Bacillus particularly for B. cereus (Gao et al, 2018;Fiedler et al, 2019;Park et al, 2020), in contrast very few was reported for B. licheniformis (Jeong et al, 2017;Meneghetti et al, 2018). Because of the limitation of data which is available about the resistance of B. licheniformis and to provide a guidance value to clinicians encountering possibly B. licheniformis infections; this study was aimed to detect the antibiotic resistance profile of local thermophilic B. licheniformis isolated from soil in Maysan Province, Iraq.…”
Section: Reported Cases Have Suggested That Lichenysinmentioning
confidence: 99%